Kecenderungan Stockholm Syndrome pada Perempuan Korban Kekerasan dalam Berpacaran di Kota Makassar - Nurul Khairaat; Sitti Murdiana; Haerani Nur (CV. Ulil Albab Corp, 2023)
In several cases of dating violence, some of woman who are victims choose persist and even feel that they are a stronger attachment to their partner. This phenomenon is known as the Stockholm Syndrome. Graham, Rawlings, Ihms, Latimer, Foliano, Thompson, and Hacker (1995) explained that Stockholm Syndrome is a psychological paradox condition that creates a strong bond between victims and perpetrators of violence. This study aims to find out what situations support the emergence of Stockholm Syndrome in women victims of violence in dating who choose to survive. This study uses a qualitative method with a case study approach. Data collection was done by interview and documentation. The research participants were six people, namely two subjects. The data were analyzed using a theory driven thematic analysis technique which refers to the theory of Graham, et al. Based on the results of the study, it was found that women victims of violence in dating experienced four situations that gave rise to stockholm syndrome in themselves, namely physical and psychological threats, small kindnesses given by their partners, isolation of victims from the outside world, and the inability of the victim to escape from the relationship.The results of this study can be used as a reference for formulating an intervention program for women who cannot leave a relationship full of violence.